Pengetahuan Remaja Terhadap Proses Terbentuknya Bunyi Bahasa - Dinda Fakhira; Novia Katingal Maharani; Salwa Putri Rahmadani; Hilaliyah, Tatu Hilaliyah (BADAN PENERBIT STIEPARI PRESS, 2024)
Language is a communication tool used by humans to communicate with each other and exchange information, in the form of a sound symbol system produced by human speech. Currently, there are still many teenagers who underestimate the Indonesian language. The purpose of this study was to find out how large the percentage of teenagers who understand one of the materials related to linguistics is about the process of forming language sounds. The method used is a quantitative method using several teenagers as a sample through Google Forms. The result of this study is that Indonesian teenagers currently have little knowledge and understanding related to learning Indonesian. However, in the process of producing the sounds of this language, there were some that were answered correctly by all respondents. This is because the respondents tried to practice the results of the sound of the language when answering questions.